Perancangan Rangkaian Pengali Bilangan Binner Menggunakan Digital Electronics Education and Design Suite Simulator - Laily Muntasiroh; Ilham Yustar Afif (Website, 2023)
The research aim to determine the effectiveness of the Digital Electronics Education and Design Suite Simulator to design a series of binary multipliers. This research methode begins by determining the problem boundary, where this binary number multiplier circuit is only able to perform 2 (two) bit binary multiplication operation. So the minimum value of the multiplication results is 0000 with a decimal value of 0 to 1111 with a decimal value of 15. The design is done by simplifying the problem by using the Boolean theorem. The results of this research is the construction of simulation circuit that can be used to perform multiplication operation 2 (two) binary numbers. Simplification of the circuit with the Boolean theorem method using Digital Electronics Education and Design Suite Simulator is able effectively design series of binary multipliers with an accuracy value of 100%.